Characteristics and performance of rutile/anatase/brookite TiO2 and TiO2–Ti2O3(H2O)2(C2O4)·H2O multiphase mixed crystal for the catalytic degradation of emerging contaminants. Issue 6 (22nd January 2020) - Hu, Kangkai; E, Lei; Zhao, Dan; Li, Yajing; Zhao, Wei; Rong, Hui
Abstract : The as-synthesized rutile/anatase TiO2 and rutile/anatase/brookite TiO2 –Ti2 O3 (H2 O)2 (C2 O4 )·H2 O, particularly rutile/anatase TiO2, showed excellent catalytic oxidation of organic contaminants (MO and HBA). Abstract : Rutile TiO2 and binary/ternary/quaternary the TiO2 –Ti2 O3 (H2 O)2 (C2 O4 )·H2 O mixed crystal possessing self-assembled morphology and serving as catalysts for the photocatalytic degradation of organic pollutants or as photoanodes for photoelectrochemical (PEC) water splitting have been prepared by in situ growth via changing the concentration of potassium titanyl oxalate. The rutile/anatase TiO2 with mesoporous structure has a specific surface area of 27.896 m 2 g −1 and an average pore size of 3.411 nm. The sample has a relatively more regular self-assembly morphology after heat-treatment at different temperatures; however, its photocatalytic activity is reduced. Excellent catalytic oxidation of methyl orange (MO) and hydroxylbenzoic acid (HBA) is observed on the as-synthesized samples, wherein rutile/anatase TiO2 and rutile/anatase/brookite TiO2 –Ti2 O3 (H2 O)2 (C2 O4 )·H2 O show excellent photocatalytic activity under UV-light. With the novel TiO2 –Ti2 O3 (H2 O)2 (C2 O4 )·H2 O mixed crystal catalyst, this study illustrates the photocatalysis mechanism of a multiphase mixed crystal for the removal of emerging contaminants in water. Based on the Mott–Schottky, XPS and energy band structure data, we consider that an indirect Z -scheme transmission mode is generated between rutile/anatase TiO2 or TiO2 –Ti2 O3 (H2 O)2 (C2 O4 )·H2 O mixed crystal, wherein the photo-induced electrons in rutile TiO2 combined with the holes in anatase TiO2 or Ti2 O3 (H2 O)2 (C2 O4 )·H2 O, leading to enhanced charge carrier extraction and utilization upon photoexcitation.